Evaluation of persons with suspected lumbosacral and cervical radiculopathy: Electrodiagnostic assessment and implications for treatment and outcomes (Part II). Issue 4 (26th July 2020) - Dillingham, Timothy R.; Annaswamy, Thiru M.; Plastaras, Christopher T.
Abstract: The electrodiagnostic (EDX) examination with needle electromyography (EMG) is the most important means of testing for radiculopathy. This test has modest sensitivity but high specificity and complements imaging of the spine. In this second of a two‐part review, the implications of electrodiagnostic findings for diagnosis and clinical management of persons with radiculopathy are reviewed. An EMG confirmed lumbosacral radiculopathy is associated with better clinical outcomes for persons undergoing aggressive conservative management. A positive EMG test portends a better clinical response to epidural corticosteroid injections. If a person undergoes spine surgery, a positive pre‐operative EMG for radiculopathy is also associated with better outcomes. Abstract : See article on pages 462–473 in this issue .